Tribological properties of copper-based composites with copper coated NbSe2 and CNT. (15th June 2015) - Chen, Beibei; Yang, Jin; Zhang, Qing; Huang, Hong; Li, Hongping; Tang, Hua; Li, Changsheng
Graphical abstract: Morphology of copper coated NbSe2 and CNT; friction coefficient and wear rate of copper-based composites. Highlights: NbSe2 and CNT were coated with copper layers by the means of electroless plating. The mechanical and tribological properties of copper composites were studied. The enhancement mechanisms of copper coated NbSe2 and CNT were proposed. Copper–copper coated (12 wt.%NbSe2 –3 wt.%CNT) composite had the best wear resistance. Abstract: Copper-based composites with copper coated NbSe2 and/or CNT were fabricated by the powder metallurgy technique. The morphology and phase composition of copper coated NbSe2 and carbon nanotube (CNT) were observed using high solution transmission electronic microscope (HRTEM), scanning electronic microscope (SEM equipped with EDS) and X-ray diffraction (XRD). The density, hardness, and bending strength of as-prepared copper-based composites were measured, and their tribological properties were investigated using UMT-2 tester. Results indicated that all copper-based composites showed decreased density and bending strength, but increased hardness in comparison with copper matrix. Besides, the incorporation of copper coated NbSe2 improved the friction-reducing and anti-wear properties of copper matrix. Addition of copper coated CNT greatly enhanced the mechanical and tribological properties. In particular, when the content of copper coated CNT was 3 wt.%, the corresponding composite exhibited the best tribological properties. This was because NbSe2 was distributed chaotically in matrix, which greatly improved the friction-reducing property of copper, while CNT with superior mechanical strength enhanced the wear resistance by increasing the load-carrying capacity. More importantly, copper layers coated on NbSe2 and CNT favored the good interfacial combination between fillers and copper matrix showing beneficial effect for the stresses transferring from matrix to fillers.